PENGARUH TERAPI DZIKIR UNTUK MENGURANGI KECEMASAN BELAJAR SISWA MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 12 PEKANBARU - Rahayu, Sri Rizky; Arlizon, Raja; Putra, Roby Maiva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Learning anxiety is a feeling of tension, worry and fear of something that will happen, these feelings interfere with the implementation of various tasks and activities in learning where learning anxiety will affect physical, emotional and mental cognitive conditions. One way to reduce anxiety is to use Dhikr therapy. The purpose of this study was to describe students' learning anxiety before and after being given Dhikr therapy through group guidance, to determine differences in student learning anxiety before and after being given Dhikr therapy through group guidance and to find out the influence of Dhikr therapy through group guidance on reducing student learning anxiety. This research is an experimental quantitative study with the approach of one group pre-test and post-test subjects in this study were 8 students taken by purposive sampling technique with the questionnaire results. The results showed that: (1) students 'anxiety before being given Dhikr therapy through group guidance were mostly in the high category, students' anxiety after being given Dhikr therapy through group guidance were mostly in the low category. (2) There is a significant difference between student learning anxiety before and after being given Dhikr Therapy through group guidance which shows a decrease in student learning anxiety. (3) There is a significant effect of Dhikr therapy on student learning anxiety through group guidance.Key Words: Therapy, Dhikr Asmaul Husna, Learning Anxiety